Governments, managers and industrial relations - Ferner, Anthony (New York, 1988)
Faced with economic crisis and escalating public expenditure, governments throughout Europe have become increasingly concerned with the role of public enterprises in the economy. There have been growing demands for greater efficiency and commercialism in these enterprises. This book explores the ways in which public enterprise industrial relations have responded to the resulting changes in their political and economic environment. Using British and Spanish railways as examples, the author sets out to show how these general tendencies have been modified by different traditions, government ideologies and industrial relations and institutions, and by political bargaining or exchange between governments, managements and trade unions. The book aims to provide an exploration of the distinctive logic of the public sector, a relatively neglected area of modern industrial relations, with implications for current policy concerns such as privatization.
Keywords: Government business enterprises